Patterns of Treatment and Outcomes in Older Men With Penile Cancer: A SEER Dataset Analysis - Bourlon, Maria T.; Verduzco-Aguirre, Haydee; Molina, Elizabeth; Meyer, Elisabeth; Kessler, Elizabeth; Kim, Simon P.; Spiess, Philippe E.; Flaig, Thomas (Frontiers in Oncology, 2022)
Purpose: To evaluate clinicopathologic and treatment characteristics from a population-based cohort of penile cancer, with an emphasis in older adults, due to incomplete evidence to guide therapy in this age subgroup. Materials and Methods: Patients with malignant penile tumors diagnosed 2004-2016 were identified in the Surveillance, Epidemiology and End Results Program (SEER)-18 dataset. Demographic and treatment characteristics were obtained. Population was analyzed by age at diagnosis (<65 vs ≥65 years). We examined univariate associations between age groups with Chi-square analysis. To study survival, we calculated Kaplan-Meier survival curves, but due to the high number of competing events, we also performed a univariate competing risk analysis using the cumulative incidence function, and a multivariate analysis using the Fine-Gray method. We also described competing mortality due to penile cancer and other causes of death. Results: We included 3,784 patients. Median age was 68 years, 58.7% were aged ≥65. Older patients were less likely to have received chemotherapy (p<0.001), primary site surgery (p = 0.002), or therapeutic regional surgery (p <0.001). Median overall survival (OS) in patients <65 years was not reached (95% CI incalculable) vs 49 months in those ≥65 years (95% CI 45-53, p <0.0001). On univariate analysis, age was associated with a lower incidence of penile cancer death. On multivariate analysis, stage at diagnosis, and receipt of primary site surgery were associated with a higher incidence of penile cancer death. Estimated penile cancer-specific mortality was higher in patients <65 years in stages II-IV. Estimated mortality due to other causes was higher in older patients across all stages. Conclusions: Older patients are less likely to receive surgery, chemotherapy and radiotherapy for penile cancer. Primary surgical resection was associated with better penile cancer-specific mortality on multivariate analysis. Competing mortality risks are highly relevant when considering OS in older adults with penile cancer. Factors associated with undertreatment of older patients with penile cancer need to be studied, in order to develop treatment strategies tailored for this population.